Specific plasticity of the anemone Anthopleura hermaphroditica to intertidal and subtidal environmental conditions of the Quempillén estuary - Víctor M. Cubillos; Felipe E. Ramírez; Daniela A. Mardones-Toledo; Nelson Valdivia; Oscar R. Chaparro; Jaime A. Montory; Edgardo A. Cruces (PLoS ONE, 2023)
The cellular capacity of marine organisms to address rapid fluctuations in environmental conditions is decisive, especially when their bathymetric distribution encompasses intertidal and subtidal zones of estuarine systems. To understand how the bathymetric distribution determines the oxidative damage and antioxidant response of the estuarine anemone Anthopleura hermaphroditica, individuals were collected from upper intertidal and shallow subtidal zones of Quempillén River estuary (Chile), and their response analysed in a fully orthogonal, multifactorial laboratory experiment. The organisms were exposed to the effects of temperature (10°C and 30°C), salinity (10 ppt and 30 ppt) and radiation (PAR, > 400–700 nm; PAR+UV-A, > 320–700 nm; PAR+UV-A+UV-B, > 280–700 nm), and their levels of lipid peroxidation, protein carbonyl and total antioxidant capacity were determined. The results indicated that the intertidal individuals of A. hermaphroditica presented higher levels of tolerance to the stressful ranges of temperature, salinity, and radiation than individuals from the subtidal zone, which was evident from their lower levels of oxidative damage to lipids and proteins. These results were consistent with increased levels of total antioxidant capacity observed in subtidal organisms. Thus intertidal individuals could have greater plasticity to environmental variations than subtidal individuals. Future studies are needed to understand the mechanisms underlying stress adaptation in individuals from this estuarine anemone subjected to different environmental stressors during their life cycles.